1979
DOI: 10.1038/281122a0
|View full text |Cite
|
Sign up to set email alerts
|

A structurally abnormal insulin causing human diabetes

Abstract: Insulin isolated from the pancreas of a diabetic patient with fasting hyperinsulinaemia showed decreased activity in binding to cell membrane insulin receptors and in stimulating cellular 2-deoxyglucose transport and glucose oxidation. Chemical studies suggest that the isolated hormone is a mixture of normal insulin and an abnormal variant which contains a leucine for phenylalanine substitution at position 24 or 25 of the insulin B-chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1
2

Year Published

1981
1981
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(88 citation statements)
references
References 24 publications
2
83
1
2
Order By: Relevance
“…The earlier described mutations primarily affected the biological activity of the resultant (pro)insulin molecules but did not impair their biosynthesis significantly, leading to impaired clearance accompanied by hyperinsulinemia and hyperproinsulinemia (16,17). They only resulted in diabetes in the presence of insulin resistance and in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier described mutations primarily affected the biological activity of the resultant (pro)insulin molecules but did not impair their biosynthesis significantly, leading to impaired clearance accompanied by hyperinsulinemia and hyperproinsulinemia (16,17). They only resulted in diabetes in the presence of insulin resistance and in adults.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, amino-acid substitutions within these regions have been identified in the insulins from © 1997 International Union of Crystallography Printed in Great Britain -all rights reserved three individuals in whom genetic mutations resulted in the secretion of abnormal hormones associated with diabetes (Tager et al, 1979(Tager et al, , 1980Shoelson, Fickova et al, 1983;Haneda, Chan, Kowk, Rubenstein & Steiner, 1983), insulin Chicago (B25-Phe--~B25-Leu), insulin Los Angeles (B24-Phe--->B24-Ser), and insulin Wakayama (A3-Val--->A3-Leu). The structural analysis of a A1-B29 cross-linked insulin, which was completely inactive, indicates that its conformation is nearly same as that of native insulin (Derewenda et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…By the techniques of protein chemistry and recombinant DNA technology, the abnormal insulins from two of these individuals have been identified as human insulin B25 (Phe -Leu) (human [LeuB25]-insulin, insulin Chicago) (1)(2)(3)(4)(5) and human insulin B24 (Phe -Ser) (human [SerB24]_ insulin, insulin Los Angeles) (1,6,7); the structure of the abnormal insulin from the third remains to be determined. Because small amounts of normal insulin (in addition to large amounts of abnormal insulin) were detected in the serum of all three individuals (1), and because restriction endonuclease mapping has shown that two have both normal and abnormal insulin gene alleles (1,(4)(5)(6), it seems that normal and abnormal insulin gene alleles are coexpressed in affected subjects.…”
Section: Introductionmentioning
confidence: 99%